Reliability of a Qualitative Movement Assessment Tool During a Single Leg Triple Hop. Issue 5 (31st May 2022) - Epstein, Eli; Huse, Casey; Link, Meredith; Witte, Katherine; Pontis, Veronica; Verdoni, Ryder; Greenberg, Elliot
Background: Single leg hop tests are commonly used to determine readiness for return to sport following anterior cruciate ligament reconstruction (ACLR). A common criticism of hop tests is their inability to account for quality of movement errors, which may be associated with increased risk of re-injury. The Qualitative Analysis of Single Leg Squat (QASLS) tool was originally developed to score quality of movement during a single leg squat. The usefulness of this tool for identifying quality of movement errors during single leg hopping has not been assessed. Hypothesis/Purpose: The purpose of this study was to determine the inter and intra-rater reliability of the QASLS tool during a single leg triple hop and explore if differences in reliability existed between novice and experienced clinicians. Methods: Subjects 10-24 years-old and ≥6-months post ACLR were eligible for this study. Subjects were recorded performing a maximal effort single leg triple hop on each limb. Recordings were viewed individually by five raters, two board-certified sports clinical specialists, and three doctor of physical therapy students in their 2 nd year of education. All raters were trained in the use of the QASLS tool during a single online training presentation. Raters were blinded to surgical limb and utilized the QASLS to rate the final landing of the triple hop task. Intraclass correlation coefficient (ICC) was calculated to measure reliability of the QASLS on the surgical limb. Wilcoxon signed-rank test was utilized to assess if differences in QASLS scores existed between limbs. Results: 20 subjects (mean age 16.5, 60% female) participated in this study. The cumulative inter-rater reliability of the surgical limb was moderate (ICC: 0.703) and little difference was seen between experienced and novice raters with ICCs of 0.703 and 0.603, respectively. Intra-rater reliability was better, with a cumulative ICC of 0.857 and with experienced clinicians demonstrating slightly higher reliability (ICC 0.891) than novice clinicians (ICC 0.831). The mean QASLS scores for the surgical limb and nonsurgical limbs were 5.2 and 5.4, respectively, and there was no statistically significant difference between scores (P=0.64). Conclusions: The QASLS tool offers moderate to good inter and intra-rater reliability for evaluating quality of movement errors during a single leg triple hop, regardless of rater experience level. Interestingly, surgical limb did not show any difference in quality of movement compared to the nonsurgical limb. Table 1. Interrater Reliability Table 1.2 Intrarater Reliability